The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/bph.15309
|View full text |Cite
|
Sign up to set email alerts
|

Early or deferred initiation of efavirenz during rifampicin‐based TB therapy has no significant effect on CYP3A induction in TB‐HIV infected patients

Abstract: Background and Purpose: In TB-HIV co-infection, prompt initiation of TB therapy is recommended but anti-retroviral treatment (ART) is often delayed due to potential drug-drug interactions between rifampicin and efavirenz. In a longitudinal cohort study, we evaluated the effects of efavirenz/rifampicin co-treatment and time of ART initiation on CYP3A induction. Experimental Approach: Treatment-naïve TB-HIV co-infected patients (n = 102) were randomized to efavirenz-based-ART after 4 (n = 69) or 8 weeks (n = 33)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…We also showed that cases had significantly elevated HOMA-IR, FSG, FSI, and TG levels than controls, indicating the presence of GMDs. The overall observed genotype and allele frequency proportions were similar to the findings of previous studies from Ethiopia [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…We also showed that cases had significantly elevated HOMA-IR, FSG, FSI, and TG levels than controls, indicating the presence of GMDs. The overall observed genotype and allele frequency proportions were similar to the findings of previous studies from Ethiopia [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…Studies in primary human hepatocytes have indicated that efavirenz autoinduction is non-linear, and timeand concentration-dependent [39,40]. Using an endogenous marker, we previously monitored the time course and extents of CYP3A and CYP2B6 induction among adult HIV patients from Tanzania [41][42][43], Uganda [16], and Ethiopia [31,33,35]. Results from adult HIV-infected patients indicate that efavirenz autoinduction is long-term and significantly reduces its plasma concentration over time, particularly among the CYP2B6*1/*1 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from whole blood samples using a QIAamp DNA Blood Midi Kit (Spin Protocol) (Qiagen GmbH, Hilden, Germany). Genotyping for common functional variant alleles in five genes relevant for efavirenz disposition was conducted by real-time PCR using Taqman ® assay reagents for allelic discrimination (Applied Biosystems Genotyping Assay) as described previously [19,35]. Common functional variant alleles were selected for genotyping based on the reported impact on enzyme activity and relevance for the black-African population.…”
Section: Genotyping For Cyp2b6 Cyp3a5 Slco1b1 Abcb1 and Ugt2b7mentioning
confidence: 99%
“…However, when normalized to cortisol, the variation is no longer significant within the day (Lee, 1995). Similarly, plasma 4β-hydroxycholesterol, another CYP3A metabolite, is ideally normalized to cholesterol in order to provide more robust data (Mao et al, 2017;Aklillu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%